Туала сяртчы: школа театръёслы юрттэт: сценарийёс, сценкаос, пьеса / Ульфат Бадретдинов - Бадретдинов Ульфат Шайхутдинович (Удмуртия, 2023)
Экземпляры: КР (20231002) / Инвентарный номер: 1126414 / Цена: / Сис.шифр: 84(2=664.1) / Авт.знак: Б 15 / ГРНТИ: 17 / ББК: 84(2=664.1)-6